A comparison of Traditional Vs Digital Marketing approach in the NBFIs of Bangladesh with reference to IPDC Finance Limited - Abedin, Tasnim (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2020.